Review of techniques for extraction of bilingual lexicon from comparable corpora - Singh Lehal, Manpreet; Ajit Kumar, Dr; Vishal Goyal, Dr (International Journal of Engineering and Technology, 2018)
Bilingual lexicons are important resources for performing a number of bilingual tasks in machine translation (MT) and cross-language in-formation retrieval (CLIR). Since the manual building of bilingual extraction is a tedious affair, researchers have focused upon the automatic extraction of bilingual lexicons from corpora. Another issue is the use of parallel and comparable corpora for extraction. Much success has been achieved in the use of parallel corpora but it is only available for a few language pairs and for limited domains. Therefore, the use of comparable corpora comes as an alternative but a lot need to be done in this field. The paper presents a review of different techniques and methods, which have been used for automatic extraction of bilingual lexicon suggesting that an integrated approach can give better results than using individual approaches. The paper also contains a proposed method for extraction of bilingual method using a combined approach.Â Â